Queer theology: beyond apologetics - Tonstad, Linn Marie (Cascade companions, 2018)
What is queer theology? --Apologetic strategies --Theology, sexuality, and the question of queer --Money, sex, and God: Althaus-Reid's queer theology --Queer theologies to come.